Auditory perceptual analysis of the voice of the teachers of the Faculty of Education Sciences – UNIFÉ - Granda Tiravanti, María Teresa (2016)
The objective of the present work was to determine how the voice quality of the teachers of the Faculty of Education of UNIFÉ is found. This present research is a simple descriptive study. The sample has 35 university teachers whose ages oscillate among 20 and 73 years; and between 04 and 53 years of service. A survey and an auditory perceptual protocol were evaluated individually. The auditory perceptual analysis evaluated: a) Pitch, b) Loudness, c) Maximum phonation time, d)Vocal quality of the participants. In most of the teachers we found vocal disorders. It is evident that some teachers introduced severe Pitch, as well as teachers with strong and weak loudness. With regard to the maximum phonation time, they presented an average under the standard. In terms of vocal quality, most teachers presented a right voice; nevertheless, teachers were found with hoarse, whispered and infantilized voice. In the relation of the service time and the voice quality, there was no relation with these parameters. Most of the teachers correspond to 77.1% obtained vocal parameters within normal  limits.